Sex-dimorphic landing mechanics and their role within the noncontact ACL injury mechanism: evidence, limitations and directions - Beaulieu, M. L.; McLean, S. G. (Sports Medicine, Arthroscopy, Rehabilitation, Therapy & Technology (SMARTT), 2012)
Anterior cruciate ligament (ACL) injuries continue to present in epidemic-like proportions, carrying significant short- and longer-term debilitative effects. With females suffering these injuries at a higher rate than males, an abundance of research focuses on delineating the sex-specific nature of the underlying injury mechanism. Examinations of sex-dimorphic lower-limb landing mechanics are common since such factors are readily screenable and modifiable. The purpose of this paper was to critically review the published literature that currently exists in this area to gain greater insight into the aetiology of ACL injuries in females and males. Using strict search criteria, 31 articles investigating sex-based differences in explicit knee and/or hip landing biomechanical variables exhibited during vertical landings were selected and subsequently examined. Study outcomes did not support the generally accepted view that significant sex-based differences exist in lower-limb landing mechanics. In fact, a lack of agreement was evident in the literature for the majority of variables examined, with no sex differences evident when consensus was reached. The one exception was that women were typically found to land with greater peak knee abduction angles than males. Considering knee abduction increases ACL loading and prospectively predicts female ACL injury risk, its contribution to sex-specific injury mechanisms and resultant injury rates seems plausible. As for the lack of consensus observed for most variables, it may arise from study-based variations in test populations and landing tasks, in conjunction with the limited ability to accurately measure lower-limb mechanics via standard motion capture methods. Regardless, laboratory-based comparisons of male and female landing mechanics do not appear sufficient to elucidate causes of injury and their potential sex-specificity. Sex-specific in vivo joint mechanical data, if collected accurately, may be more beneficial when used to drive models (e.g., cadaveric and computational) that can additionally quantify the resultant ACL load response. Without these steps, sex-dimorphic landing mechanics data will play a limited role in identifying the aetiology of ACL injuries in women and men.